ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR PERTANIAN DI KABUPATEN LAMONGAN - Halimatus Sakdiyah; Taufiq , M. (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
The amount of labor employed in an economic sector is known as labor absorption. The ability of a region to absorb labor is very important for the success of regional development strategies. So the purpose of this study is to determine and analyze whether there is an effect of agricultural sector GRDP, agricultural land area, real wages of farm laborers, and farmer exchange rates on labor absorption in the agricultural sector in Lamongan Regency using the 2007-2021 time period. The data used is secondary data in the form of time series (annual) obtained from the publication of BPS Lamongan Regency and East Java Province. The analysis method used is multiple linear regression with the help of the SPSS data processing computer program. The results found that agricultural sector GRDP, agricultural land area, real wages of farm laborers, and farmer exchange rate together have a positive influence on employment. Variables of agricultural GDP and real wages of farm laborers have a negative influence on employment in the agricultural sector. Meanwhile, agricultural land area and farmer exchange rate have no effect on the absorption of agricultural sector labor in Lamongan Regency.